Coexistence of Colorectal Adenomas and Coronary Calcification in Asymptomatic Men and Women - Yun, Kyung Eun; Chang, Yoosoo; Rampal, Sanjay; Zhang, Yiyi; Cho, Juhee; Jung, Hyun Suk; Kim, Chan Won; Jeong, Chul; Cainzos-Achirica, Miguel; Zhao, Di; Pastor-Barriuso, Roberto; Shin, Hocheol; et al. (Lippincott, Williams & Wilkins, 2017)
Goals: Because of shared risk factors between clinically manifest cardiovascular disease and colorectal cancer, we hypothesized the coexistence of subclinical atherosclerosis measured by coronary artery calcium (CAC) and colorectal adenoma (CRA) and that these 2 processes would also share common risk factors. Background: No study has directly compared the risk factors associated with subclinical coronary atherosclerosis and CRA. Study: This was a cross-sectional study using multinomial logistic regression analysis of 4859 adults who participated in a health screening examination (2010 to 2011; analysis 2014 to 2015). CAC scores were categorized as 0, 1 to 100, or >100. Colonoscopy results were categorized as absent, low-risk, or high-risk CRA. Results: The prevalence of CAC>0, CAC 1 to 100 and >100 was 13.0%, 11.0%, and 2.0%, respectively. The prevalence of any CRA, low-risk CRA, and high-risk CRA was 15.1%, 13.0%, and 2.1%, respectively. The adjusted odds ratios (95% confidence interval) for CAC>0 comparing participants with low-risk and high-risk CRA with those without any CRA were 1.35 (1.06-1.71) and 2.09 (1.29-3.39), respectively. Similarly, the adjusted odds ratios (95% confidence interval) for any CRA comparing participants with CAC 1 to 100 and CAC>100 with those with no CAC were 1.26 (1.00-1.6) and 2.07 (1.31-3.26), respectively. Age, smoking, diabetes, and family history of CRC were significantly associated with both conditions. Conclusions: We observed a graded association between CAC and CRA in apparently healthy individuals. The coexistence of both conditions further emphasizes the need for more evidence of comprehensive approaches to screening and the need to consider the impact of the high risk of coexisting disease in individuals with CAC or CRA, instead of piecemeal approaches restricted to the detection of each disease independently.